Predictors of the Prevalence of Dyslipidemia and Influencing Factors for Young Health Examination Cohort: A Cross-Sectional Survey - Zhang, Hui; Kwapong, William Robert; Shao, Meng-Meng; Yan, Jue-Yue; Lin, Xian-Da; Chen, Bo-Bei; Chen, Ke-Yang (Frontiers in Public Health, 2020)
Abstract Objectives: To estimate the prevalence of dyslipidemia and its associated influence factors in young adults in southeastern coastal area of China. Methods:This study used a cross-sectional survey. We conducted this study among 7,859 young people with health examination in the three hospitals in Wenzhou, Zhejiang province between April 2017 and December 2018.All subjects completed a questionnaire during face-to-face interviews, examined for anthropometric measurements and biochemical tests. Continuous data were presented as means ± standard deviations (SD) and compared using the Student’s t-test. Categorical variables were presented as proportions. The associated influence factors of dyslipidemia were evaluated through multivariate logistic regression. Results: The prevalence of dyslipidemia in young adults was 34.11% with 7.1%, 15.0%, 22.9%, and 4.0% for hypercholesteremia, hypertriglyceridemia, low high-density lipoprotein cholesterol, high low-density lipoprotein cholesterol respectively. The mean concentrations of total cholesterol, triglyceride, HDL, and LDL were 4.66 ± 0.18 mmol/L, 1.69 ± 0.07mmol/L, 1.21 ± 0.05 mmol/L, and 2.69 ± 0.11 mmol/L. The presence of dyslipidemia was significantly associated with increasing age, men gender (OR: 1.85, 95% CI: 1.39-2.21), smoking(OR: 2.02, 95% CI: 48 1.98-2.13), alcohol consumption (OR: 1.33, 95% CI: 1.16-1.63), overweight or obesity (OR: 2.01, 95% CI: 1.79-2.41) and intellectual work (OR: 1.36, 95% CI: 1.11-1.72). Conclusion: The prevalence of dyslipidemia among young adults aged from 18 to 45 in the southeastern coast of China was high. To prevent dyslipidemia at early age, it is essential to conduct effective intervention programs aimed at risk factors and to implement routine screening programs.